In vitro cytotoxic activity of Brazilian Middle West plant extracts - Mahmoud, Talal Suleiman [UNESP]; Marques, Maria Rita; Pessoa, Cláudia do Ó; Lotufo, Leticia V. C.; Magalhães, Hemerson I. F.; Moraes, Manoel O. de; Lima, Dênis P. de; Tininis, Aristeu G.; Oliveira, Jose Eduardo de [UNESP] (Sociedade Brasileira de Farmacognosia, 2011)
Cytotoxic activity of eight plant extracts, native from the Mid-West of Brazil comprising Cerrado, Pantanal and semideciduous forest, was evaluated for MDA-MB-435, SF-295, and HCT-8 cancer cell strains. A single 100 µg.mL-1 dose of each extract was employed with 72 h of incubation for all tests. Doxorubicin (1 µg.mL-1) was used as the positive control and the MTT method was used to detect the activity. Cytotoxicity of distinct polarities was observed in thirty extracts (46%), from different parts of the following species: Tabebuia heptaphylla (Vell.) Toledo, Bignoniaceae, Tapirira guianensis Aubl., Anacardiaceae, Myracrodruon urundeuva Allemão, Anacardiaceae, Schinus terebinthifolius Raddi, Anacardiaceae, Gomphrena elegans Mart., Amaranthaceae, Attalea phalerata Mart. ex Spreng., Arecaceae, Eugenia uniflora L., Myrtaceae, and Annona dioica A. St.-Hil., Annonaceae. Extracts of at least two tested cell strains were considered to be highly active since their inhibition rate was over 75%.
Keywords: Brazilian Middle-west plants; cytotoxicity; cancer cell lines